Gambaran Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Terapi Continuous Ambulatory Peritoneal Dialysis Di RSUD Arifin Achmad Provinsi Riau Dengan Menggunakan Kuesioner KDQOL-SFTM - Rizqina Putri; Ligat Pribadi Sembiring; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Chronic renal failure is an end stage of renal disease that can be treated by dialysis, which one of them is Continuous Ambulatory Peritoneal Dialysis (CAPD). CAPD is a dialysis technique uses peritoneal membrane as dialysis membrane that splits between dyalisate in peritoneal membrane with blood plasm in peritoneal vessels. CAPD as a theraphy for chronic renal failure patients can be examined by KDQOL-SFTM questionnaire to measures its effect on patients’ quality of life. This research helds on purpose to get a representation of Continuous Ambulatory Peritoneal Dialysis (CAPD) patients’ life quality. This is a descriptive method of research with cross sectional approachment and had implemented on February 2014. About 47 chronic renal failure patients have been undergoing CAPD therapy. Research results showed most of respondents is dominated by male respondents (59,57%). Results from respondent by age category indicated that category 18-44 years old and category 45-64 years old are relatively equal ini amount. Category by ethnic showed that most of respondents are Malay ethnic (31,91%). Respondents have been educated and got undergraduated and degree: D1/D2/D3/S1 (53,19%). Most of respondents have been married (93,61%) and work as a housewife, retired and unemployed (36,17%). CAPD has been used as theraphy for about 1-5 years by most respondents (72,34%). Most chronic renal failure patient who undergo CAPD therapy at RSUD Arifin Achmad Riau Province (76,59%) have hight value of quality of lifeKey word: chronic renal failure, Continuous Ambulatory Peritoneal Dialysis , quality of life